Development of composite high entropy-medium entropy alloy coating. (1st January 2023) - Meghwal, Ashok; Singh, Surinder; Sridar, Soumya; Xiong, Wei; Hall, Colin; Munroe, Paul; Berndt, Christopher C.; Ang, Andrew Siao Ming
Abstract: The viability of adapting HEAs or MEAs with single-phase structures, such as either FCC or BCC phases, for industrial applications is challenging due to the trade-offs in properties between different phases. Therefore, a novel high entropy alloy-medium entropy alloy composite coating based on a hard metal concept was designed using a CALPHAD approach, followed by experimental validation that included microstructural, mechanical and tribological analysis. A harder BCC/B2-based AlCoCrFeNi HEA powder was blended with a softer and more ductile FCC-based CoCrFeNi MEA to manufacture a composite coating using the HVOF process. The phase prediction, using Scheil simulation, which depicts non-equilibrium processing conditions experienced during the HVOF process, suggested the development of BCC, B2 and FCC phases, complementing XRD phase projections. The composite coating exhibited higher hardness than either single phase AlCoCrFeNi or CoCrFeNi coatings and achieved superior wear resistance under dry sliding conditions at elevated temperature, thereby, exhibiting potential for structural applications. Graphical abstract: Image, graphical abstract